Insulin resistance is associated with new-onset cardiovascular events in nondiabetic patients undergoing peritoneal dialysis - Chang-Yun Yoon; Mi Jung Lee; Youn Kyung Kee; Eunyoung Lee; Young Su Joo; In Mee Han; Seung Gyu Han; Hyung Jung Oh; Jung Tak Park; Seung Hyeok Han; Shin-Wook Kang; Tae-Hyun Yoo (The Korean Society of Nephrology, 2014)
Background: Chronic exposure to high glucose-containing peritoneal dialysis solution and consequent abdominal obesity are potential sources of insulin resistance in patients requiring prevalent peritoneal dialysis. The aim of this study was to elucidate the prognostic values of insulin resistance on new-onset cardiovascular events in nondiabetic patients undergoing prevalent peritoneal dialysis. Methods: A total of 201 nondiabetic patients undergoing prevalent peritoneal dialysis were recruited. Insulin resistance was assessed by homeostatic model assessment of insulin resistance (HOMA-IR). The primary outcome was new-onset cardiovascular events during the follow-up period. Cox proportional hazard analysis was performed to ascertain the independent prognostic value of HOMA-IR for the primary outcome. Results: The mean age was 53.1 years and male was 49.3% (n=99). The mean HOMA-IR was 2.6±2.1. In multivariate linear regression, body mass index (β=0.169, P=0.011), triglyceride level (β=0.331, P<0.001), and previous cardiovascular diseases (β=0.137, P=0.029) were still significantly associated with HOMA-IR. During a mean follow-up duration of 36.8±16.2 months, the primary outcome was observed in 36 patients (17.9%). When patients were divided into tertiles according to HOMA-IR, the highest tertile group showed a significantly higher incidence rate for new-onset cardiovascular events compared to the lower two tertile groups (P=0.029). Furthermore, multivariate Cox analysis revealed that HOMA-IR was an independent predictor of the primary outcome (hazard ratio=1.18, 95% confidence interval=1.03-1.35, P=0.014). Conclusion: Insulin resistance measured by HOMA-IR was an independent risk factor for new-onset cardiovascular events in nondiabetic patients undergoing prevalent peritoneal dialysis.